Проблеми вдосконалення юридичної термінології в українському законодавстві - Корж, А.В.; Фонтош, Н.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье раскрыто некоторые проблемы современного становления государственно-языковой политики при правовом регулировании языковых отношений в законодательстве Украины, большое внимание уделено проблемам юридической терминологии в украинском законодательстве, поиску путей её усовершенствования. The article analyses some problems of contemporary formation of state language policy in the context of regulation of language relations in the Ukrainian legislation. The special attention is given to the issues of juridical terminology in the Ukrainian legislation, the ways of its improvement.